2008
DOI: 10.1158/1541-7786.mcr-07-2179
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' Tumor 1 Suppressor Gene Mediates Antiestrogen Resistance via Down-Regulation of Estrogen Receptor-α Expression in Breast Cancer Cells

Abstract: The antiestrogen tamoxifen has been used in the treatment of hormone-responsive breast cancer for over a decade. The loss of estrogen receptor (ER) expression is the most common mechanism for de novo antiestrogen resistance. Wilms' tumor 1 suppressor gene (WT1) is a clinically useful marker that is associated with poor prognosis in breast cancer patients; its high level expression is frequently observed in cases of breast cancer that are estrogen and progesterone receptor negative. The lack of expression of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
(24 reference statements)
2
16
1
1
Order By: Relevance
“…Though Miyoshi et al (18) found that the prognosis of patients with high WT1 expression was significantly worse than that in patients with low WT1 expression, Camcı et al failed to confirm this finding in a later study (23). In the present study, we concluded that WT1 mRNA high expression predicted poor prognosis of breast cancer patients when using 3.1 as cutoff value, which might be due to the facts that WT1 could promote proliferation, invasion, migration, response to hypoxia and drug resistance of cancer cells (19)(20)(21)(22)35,37,38).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Though Miyoshi et al (18) found that the prognosis of patients with high WT1 expression was significantly worse than that in patients with low WT1 expression, Camcı et al failed to confirm this finding in a later study (23). In the present study, we concluded that WT1 mRNA high expression predicted poor prognosis of breast cancer patients when using 3.1 as cutoff value, which might be due to the facts that WT1 could promote proliferation, invasion, migration, response to hypoxia and drug resistance of cancer cells (19)(20)(21)(22)35,37,38).…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, we found that WT1 expression was higher in ER-negative patients than in ER-positive patients, which may be explained by the fact that overexpression of WT1 directly resulted in the down-regulation of ER expression (22). In addition, our results also demonstrated that WT1 tended to be overexpressed in tumors with high histological grades.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Also, WT1 expression is significantly higher in ER-positive (luminal) than in ER-negative (basal) tumours. This finding may be of particular interest, given that WT1 has been shown to both interact with ERα and modulate its expression in vitro 55.…”
Section: Discussionmentioning
confidence: 86%
“…The cell type, its current state of development [61] and the ratio of WT1 isoform expression [62] may be crucial for WT1 to either promote or suppress tumor development. On the other hand, mammary tumors with high levels of WT1 have a poor prognosis and high levels of WT1 expression are frequently observed in cases of breast cancer that are estrogen and progesterone receptor negative [63]. WT1 expression is regulated by progesterone in a tissue dependent manner.…”
Section: Discussionmentioning
confidence: 99%